Long‐term effects of Na+/Ca2+ exchanger inhibition with ORM‐11035 improves cardiac function and remodelling without lowering blood pressure in a model of heart failure with preserved ejection fraction. (24th November 2019) - Primessnig, Uwe; Bracic, Taja; Levijoki, Jouko; Otsomaa, Leena; Pollesello, Piero; Falcke, Martin; Pieske, Burkert; Heinzel, Frank R.
Abstract : Aims: Heart failure with preserved ejection fraction (HFpEF) is increasingly common but there is currently no established pharmacological therapy. We hypothesized that ORM‐11035, a novel specific Na + /Ca 2+ exchanger (NCX) inhibitor, improves cardiac function and remodelling independent of effects on arterial blood pressure in a model of cardiorenal HFpEF. Methods and results: Rats were subjected to subtotal nephrectomy (NXT) or sham operation. Eight weeks after intervention, treatment for 16 weeks with ORM‐11035 (1 mg/kg body weight) or vehicle was initiated. At 24 weeks, blood pressure measurements, echocardiography and pressure–volume loops were performed. Contractile function, Ca 2+ transients and NCX‐mediated Ca 2+ extrusion were measured in isolated ventricular cardiomyocytes. NXT rats (untreated) showed a HFpEF phenotype with left ventricular (LV) hypertrophy, LV end‐diastolic pressure (LVEDP) elevation, increased brain natriuretic peptide (BNP) levels, preserved ejection fraction and pulmonary congestion. In cardiomyocytes from untreated NXT rats, early relaxation was prolonged and NCX‐mediated Ca 2+ extrusion was decreased. Chronic treatment with ORM‐11035 significantly reduced LV hypertrophy and cardiac remodelling without lowering systolic blood pressure. LVEDP [14 ± 3 vs. 9 ± 2 mmHg; NXT ( n  = 12) vs. NXT + ORM ( n  = 12); P  = 0.0002] and BNP levels [71 ± 12 vs. 49 ± 11 pg/mL; NXT ( n  = 12) vs. NXT + ORM ( n  = 12); P  < 0.0001] were reduced after ORM treatment. LV cardiomyocytes from ORM‐treated rats showed improved active relaxation and diastolic cytosolic Ca 2+ decay as well as restored NCX‐mediated Ca 2+ removal, indicating NCX modulation with ORM‐11035 as a promising target in the treatment of HFpEF. Conclusion: Chronic inhibition of NCX with ORM‐11035 significantly attenuated cardiac remodelling and diastolic dysfunction without lowering systemic blood pressure in this model of HFpEF. Therefore, long‐term treatment with selective NCX inhibitors such as ORM‐11035 should be evaluated further in the treatment of heart failure.